2007
DOI: 10.5144/0256-4947.2007.333
|View full text |Cite
|
Sign up to set email alerts
|

Experience with 122 consecutive liver transplant procedures at King Faisal Specialist Hospital and Research Center

Abstract: BACKGROUNDSaudi Arabia is a leading country in the Middle East in the field of deceased-donor liver transplantation (DDLT) and living-donor liver transplantation (LDLT). We present out experience with DDLT and LDLT at King Faisal Specialist Hospital and Research Center (KFSHRC) for the period from April 2001 to January 2007.PATIENTS AND METHODSWe performed 122 LT procedures (77 DDLTs and 45 LDLTs) in 118 patients (4 retransplants) during this period of time.RESULTSThe number of adult and pediatric procedures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 16 publications
3
24
0
Order By: Relevance
“…Finally, 19 published clinical cohort studies (4 prospective cohorts and 15 retrospective cohorts) were included in the meta-analysis. 6,7,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] The characteristics of the 19 included studies are presented in Table 1. All the studies were well designed to compare the 2 arms: LDLT and DDLT.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 19 published clinical cohort studies (4 prospective cohorts and 15 retrospective cohorts) were included in the meta-analysis. 6,7,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] The characteristics of the 19 included studies are presented in Table 1. All the studies were well designed to compare the 2 arms: LDLT and DDLT.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Significant heterogeneity among the 5 studies was found for RBC transfusion requirements (P 5 0.006, I 2 5 72%); therefore, a random-effect model was used to combine the data. Pooled results revealed that LDLT and DDLT 16 4 2 3 9 Shah et al 17 3 2 3 8 Al-Sebayel et al 18 3 2 3 8 Schmeding et al 19 3 2 3 8 Selzner et al 20 3 2 3 8 Freise et al 21 3 2 3 8 G omez et al 22 3 0 3 6 Gallegos-Orozco et al 23 3 2 3 8 Fisher et al 7 4 1 3 8 Lai et al 24 3 1 3 7 Shin et al 25 3 2 1 6 Merion et al 26 3 2 3 8 Li et al 27 3 2 3 8 Jain et al 28 3 2 3 8 Reichman et al 6 3 2 3 8 Jiang et al 29 3 2 3 8 Figure 2. Meta-analysis of controlled trials comparing DROs for LDLT and DDLT recipients on the basis of a random-effect model.…”
Section: Allogeneic Rbc Transfusionmentioning
confidence: 99%
“…In Saudi Arabia, where three active cadaveric liver transplant programs exist, the overall three-year graft and patient survival rates were approximately 90% and 80%, respectively, with at least 20% of the cases were due to HCV-G4. [ 24 33 34 35 36 37 ] Similarly, in Egypt, where many active living–related liver transplant programs exist and HCV-G4 represents more than 90% of cases, graft and patient survival rates were approximately 86%. [ 25 ]…”
Section: Overall Outcomementioning
confidence: 99%
“…In Saudi Arabia, hepatitis C represents approximately 29% of indications for liver transplantation, approximately 60% of which are secondary to HCV-G4. [ 24 ] HCV-G4 represents more than 90% of indications for liver transplantation in Egypt. [ 25 ] By contrast, HCV-G4 is a relatively uncommon indication for liver transplantation in the Western world.…”
mentioning
confidence: 99%
“…However, there is inadequate documentation of the natural history of HCV re-infection after liver transplantation in the Kingdom and worldwide. [238]…”
Section: Treating Special Populationsmentioning
confidence: 99%